2021
DOI: 10.1186/s13287-021-02445-z
|View full text |Cite
|
Sign up to set email alerts
|

Inter-center comparison of good manufacturing practices-compliant stromal vascular fraction and proposal for release acceptance criteria: a review of 364 productions

Abstract: Background Even though the manufacturing processes of the stromal vascular fraction for clinical use are performed in compliance with the good manufacturing practices applying to advanced therapy medicinal products, specifications related to stromal vascular fraction quality remain poorly defined. We analyzed stromal vascular fraction clinical batches from two independent good manufacturing practices-compliant manufacturing facilities, the Swiss Stem Cell Foundation (SSCF) and Marseille Univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 43 publications
(34 reference statements)
3
15
0
Order By: Relevance
“…the yield obtained by enzymatic isolation, it was similar to the average yield obtained by clinical-grade enzymatic SVF isolation recently reported to be obtained using either the leading commercial enzyme-based Celution System (Cytori Therapeutics Inc.) (n = 70) or by manual isolation (n = 294), 20 making the RBs technique highly relevant to clinical use. Importantly, however, SVF isolation using this nonenzymatic method was achieved in under 15 minutes, a drastically shorter interval than enzymatic isolation.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…the yield obtained by enzymatic isolation, it was similar to the average yield obtained by clinical-grade enzymatic SVF isolation recently reported to be obtained using either the leading commercial enzyme-based Celution System (Cytori Therapeutics Inc.) (n = 70) or by manual isolation (n = 294), 20 making the RBs technique highly relevant to clinical use. Importantly, however, SVF isolation using this nonenzymatic method was achieved in under 15 minutes, a drastically shorter interval than enzymatic isolation.…”
Section: Discussionsupporting
confidence: 81%
“…19 RBs mechanical isolation technology isolated an average 2.01 × 10 5 ± 1.2 × 10 5 SVF nucleated cells per 1 mL fat (n = 30). The yield was inferior to the yield obtained by enzymatic isolation [4.17 × 10 5 ± 1.8 × 10 5 SVF nucleated cells per 1 mL fat (n = 30)], but was similar to the average yield obtained by clinical-grade enzymatic SVF isolation recently reported to be obtained using either the leading commercial enzyme-based Celution System (Cytori Therapeutics Inc.) (n = 70) or by manual isolation (n = 294) 20 and far superior to that achieved by the wash technique [0.67 × 10 5 ± 0.51 × 10 5 SVF nucleated cells per 1 mL fat (n = 30)] (Fig. 2).…”
Section: Rbs Mechanical Isolation Achieved Human Svf Yields Comparabl...supporting
confidence: 47%
See 1 more Smart Citation
“…It has been reported that SVF cells, especially adiposederived mesenchymal stromal cells, could exert an antisclerotic association with morphea. [29][30][31] SVF gel only requires the mechanical process to eliminate most mature adipocytes and concentrate SVF cells within the adipose tissue, getting rid of using the collagenase and retaining the ECM scaffold. [32][33][34] SVF gel can be injected through a 30-G needle, which enables precise intradermal delivery, as traditional lipoaspirates cannot.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially the case when the objective is to sort the cells upstream of specific processes. One can find many examples in biomedical research [1,2], clinical diagnostic [3,4] and bioproduction field [5,6]. The common principles for cell separation are based either on the density differences or on specific biological membrane markers.…”
Section: Introductionmentioning
confidence: 99%